Hydrological dry periods versus atmospheric circulations in the lower Vistula Basin (Poland) in 1954–2018 - Bartczak, Arkadiusz; Araźny, Andrzej; Krzemiński, Michał; Maszewski, Rafał (Quaestiones Geographicae, 2022)
The paper discusses the impact of atmospheric circulation on the occurrence of droughts. The research includes mean monthly discharges for 7 rivers in 1954-2018. Dry periods were determined with Standardised Streamflow Indices (SSI-12). Additionally, the circulation type calendar for Central Poland was used to determine the atmospheric circulation indices: western zonal (W), southern meridional (S) and cyclonicity (C). The analyses indicated a variation in the duration and intensity of droughts in the rivers. 2014-2017 was the driest period with the lowest SSI-12 for most rivers and the highest number of extremely dry months. The advection of air from the West and the South prevailed and anticyclonic synoptic situations dominated over the cyclonic types. Drought spells occurred at a dominance of anticyclonic circulation, with the inflow of air from the North and with increased western zonal circulation.